Addressing challenges in promoting the use of animal-origin textile fibers for mitigating microplastic pollution on earth - Frank, Eduardo Narciso (2023)
The aim of this review is to address the issue of textile-origin microplastics and to provide possible solutions that can be propose through a scientific and development program. The constant expansion of textile production and consumption, driven by population growth and the ubiquity of fast fashion, has triggered environmental contamination resulting from the release of fiber fragments during the washing and use of clothing and household textiles. These fragments, ranging in size from 1 μm to 5 mm, pose a novel source of pollution that not only threatens the health of aquatic animals when ingested but also risks human food safety by infiltrating the food chain. Despite the growing awareness of the environmental impacts of these plastic microfibers (MP) from synthetic textiles, this study departs from conventional actions focused on mitigating microplastic pollution. Instead, it focuses on proposing specific measures to reduce MP emissions and addresses the even greater challenge of replacing these plastic microfibers with animal-origin textile fibers. This approach emerges as a promising and sustainable alternative to counteract the negative environmental impact of the contemporary fashion industry. The essence of this challenge lies in determining the competitiveness of animal-origin textile fibers against MP. To achieve this goal, specific actions are proposed, including the need to reduce both the environmental impact and costs associated with processing animal fibers. The study also emphasizes the importance of effectively highlighting the biological and textile advantages of these fibers to encourage their acceptance and adoption in the competitive textile market. This project addresses concrete strategies to promote the use of animal-origin textile fibers. It suggests optimizing the cleaning process and genetically improving these fibers, considering key aspects such as quality and color. The research also highlights the potential contribution to sustainability certification and well-being associated with the use of animal-origin textile fibers, providing a solid foundation for their adoption in the textile industry. In conclusion, this work not only departs from traditional measures focused on microplastics to address MP release but ventures into more ambitious territory by proposing increased use of animal-origin textile fibers as a path to a more sustainable fashion. Specific actions are outlined to enhance the competitiveness of these fibers in the current market, emphasizing their potential contribution to reducing textile pollution and thus strengthening the transition to more environmentally responsible practices in the fashion industry.